Rural area electrification with variable speed diesel generator and lithium-ion battery hybrid system. (5th January 2022) - Kumar, Gireesh; Babu, C.A.
A reliable energy source is an essential component of any modern society, yet substantial part of the world population experiencing energy poverty. This paper presents variable speed diesel generator (VSDG) and lithium-ion battery hybrid system for rural area electrification. This hybrid system can be efficiently and economically used for power supply in basic needs like power, water and communication (PWC) system. The proposed hybrid system constitute VSDG sets connecting to DC bus via fully controlled rectifiers serves as the main power supply sources and Lithium-ion battery pack linked to the DC bus through DC/DC converters serves as an auxiliary power supply. The variable speed concept of DGs helps to economic operation with diminished fuel consumption as its speed changes with load variation. The efficient separation of low frequency and high frequency components of load currents and its assignation to suitable sources helps to reduce the transients during load power fluctuations. One of the generators will be turned off when total power demand goes below a specified value and consequently significant fuel savings can be accomplished. The execution of proposed system is evaluated through MATLAB/Simulink software and its substantiation by experimental test bench.